ESTUDIO DE UN SISTEMA DE GESTIÓN DOCUMENTAL EN LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN. - Chantera Riascos, Jessenia Nathalie (2017)
The evolution of technology from the early forties of human history, a surprising impulse due to the design and progressive admiration for machines called computers, through the area of ​​learning domain, relatively. (Tobar, 2010) In recent years, with technological advances digital documents and expectations of document management have changed respectively. At the moment electronic document management is very convenient in terms of improving work processes, and in the combination of knowledge between instances, thus allowing organizations to acquire real possibilities for change. (Navarro, Reynalde, & Nadya Elida, 2014) One of the main difficulties that are presented in the Faculty of Education Sciences is the mismanagement of the documentation of the students since there is a lot of information loss at the moment of the information search, with the investigation we can say that there is the need to make a case study for the improvement and thus give an adequate solution. The extraordinary versatility of computing in all fields of human activity, as well as its progressive information, have made it possible for them to cross the threshold of the great centers of calculation to become the obligatory tool of the great student public in this modern society in which we develop. At the Technical University of Babahoyo activities are carried out every day, documents are handled in a row, so the increase in the use of paper is considered by what new students enter and the procedures to be performed are several. All this requires the use of paper, with the document management system improves all the services offered to the students and teachers of the Faculty of Social Juridical Sciences and Education.